Influence of Employer Branding, Employee Experience, and Organizational Commitment on Employee Performance: Evidence from PT. PLN (Persero) UP3, Palopo City - Lita Sriyanti; Haedar Haedar; Adi Firmanzah (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to analyze the influence of employer branding, employee experience, and organizational commitment on employee performance at PT. PLN (Persero) UP3 Palopo City. Methodology: The study used a quantitative approach with a survey method on 52 respondents selected through a random sampling technique. Data were collected through a questionnaire that had been tested and declared valid with a calculated r-value > r-table (0.273) and reliable with a Cronbach's alpha value for all variables > 0.60. Data analysis was conducted using multiple linear regression with the help of SPSS version 26 application. Results: The results of this study indicate that employer branding (t=0.437; sig = 0.664) and employee experience (t= 0.360; sig = 0.720) do not have a significant effect on employee performance, while organizational commitment has a positive and significant effect on employee performance with a value (t= 5.815; sig = 0.000). Simultaneously, the f-count value is 28.181 with a significant value of 0.000, which means that all three variables have a significant effect on employee performance. The coefficient of determination (R2) value of 0.638 indicates that 63.8% of employee performance variation can be explained by the research model, while 36.2% is influenced by other factors outside the model. Findings: The research findings indicate that organizational commitment is the most dominant factor in improving employee performance. Novelty & Originality: The novelty of this study lies in the simultaneous testing of the three variables in the context of the state-owned electricity sector service unit. The originality of the study is reflected in the empirical focus on PT. PLN (Persero) UP3 Palopo City, which has received limited research. Conclusions: This paper is an empirical research paper that concludes that strengthening organizational commitment is a key strategy for improving employee performance.